Efektivitas Pembelajaran PAK Dengan Metode Teams Games Tournament Berbantuan LKS Terhadap Prestasi Belajar Siswa Kelas V SD Aloysius Semarang - Victor Jendade Araujo; Yustinus Joko Wahyu Yuniarto; Anselmus Joko Prayitno (Jurnal Pendidikan Agama dan Teologi, 2023)
The low learning outcomes of students of Catholic religious education subjects SD Aloysius Semarang due to the method applied by teachers who have not used a fun method at the time of religious learning. The purpose of this study was to determine the character of responsibility by using the method of Teng-assisted worksheets can improve student completion, knowing the differences in learning achievement, to determine the character of the responsibility of the method of Teng-assisted worksheets influence terhdap learning achievement. This study uses a quantitative experimental approach True Experimental Design method with pretest-posttest control group design and sample selection by random sampling. Data analysis used regression test, independent t test, one sample t test, and N-Gain with a significant level of 5%. Data collection techniques using observation sheets with indicators: 1) doing homework regularly, 2) expressing opinions, 3) completing tasks on Schedule, 4) doing group assignments together, tests, and documentation. The results of this study showed that learning the TENG method assisted by worksheets increased the number of completed students with an empirical average of 81.25. The empirical mean of experimental class is 81.25 and control is 58.21. Through the results of the N-Gain score, the experimental class got 70.74% (quite effective), while the control got 23.18% (ineffective). The effect of responsibility on learning achievement from R square is 82.5%. It can be proven that the LKS-assisted Teng method is able to increase completed students to 25 students.